Tick Size, Share Prices, and Stock Splits - ANGEL, JAMES J. (Journal of Finance, 1997)
ABSTRACT Minimum price variation rules help explain why stock prices vary substantially across countries, and other curiosities of share prices. Companies tend to split their stock so that the institutionally mandated minimum tick size is optimal relative to the stock price. A large relative tick size provides an incentive for dealers to make markets and for investors to provide liquidity by placing limit orders, despite its placing a high floor on the quoted bid‐ask spread. A simple model suggests that idiosyncratic risk, firm size, and visibility of the firm affect the optimal relative tick size and thus the share price.